Thai Science Educators’ Perspectives on Students’ Prior Knowledge: A Documentary Research - Luecha Ladachart; Ladapa Ladachart (Science Education International, 2019)
According to constructivist theory, learning is a construction of new knowledge based on prior knowledge. As a consequence, science teachers are encouraged to take students’ prior knowledge into account. It is evident in many cases that although students’ prior knowledge is often not consistent with scientific knowledge, they may have some potential to be developed. Thus, science teachers should not consider only the limitations of students’ knowledge but also its potential. Science educators should model how to advance students’ prior knowledge. However, research is lacking in this concern as specifically related to science educators. This research uses a documentary analysis of 78 empirical studies and academic articles to examine the perspectives of Thai science educators regarding students’ prior knowledge. The results reveal that Thai science educators tend to perceive and approach students’ prior understandings as a learning obstacle rather than as a cognitive resource with which science teachers can work to facilitate students’ learning. An implication is that Thai science educators may need to be made aware of their perspectives on students’ prior knowledge to appropriately communicate to and model for science teachers.